Effect Of TiO2 Addition On The Electrical Conductivity Of Nylon-TiO2 Hybrid Membrane - Rohmah, Nurul Octavia Hijriyatur (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2020)
Current membrane technology has developed rapidly in industrial commercial interests. This has led to various studies, especially on membrane raw material innovation. Research on the measurement of electrical conductivity on nylon-TiO2 hybrid membranes has been carried out. This study aims to determine the addition of the right TiO2 mass fraction based on the electrical conductivity value. The variations in the concentration of TiO2 used were 0.5%, 1%, 3%, 5%, and 7% (w/v). The nylon-TiO2 hybrid membrane was prepared using the phase inversion method. The measurement of the electrical conductivity of the hybrid membrane was carried out using the parallel plate method. The measurement results of the nylon-TiO2 hybrid membrane showed that the electrical conductivity of the hybrid membrane increased with the addition of the mass fraction of TiO2, from (0.66 ± 0.04) × 10-9 S / cm for nylon membrane to (9.15 ± 5.71) × 10-9 S / cm for additionalmass fraction of TiO2 5% (w/v). Meanwhile, onadditionThe mass fraction of TiO2 7% (w / v) causes the electrical conductivity of the hybrid membrane to decrease, by obtaining an electrical conductivity value of(2.31 ± 0.45) × 10-9 S / cm